SEMIOTIC GAMES AND DOMESTIC GEOPOLITICS: ESTONIAN RUSSOPHONES DURING THE WAR IN UKRAINE - Makarychev, Andrey (Journal of Regional Security, 2023)
This contribution to the Forum analyzes narratives unfolding among Estonian Russian speakers who expose different attitudes towards the war in Ukraine. Empirical material comes from several media platforms and public figures whose speaking positions are representative and typical for – and duly reflect – the broad spectrum of the current Russophone discourses in Estonia. Three distinct yet interconnected discursive positions that prominently feature in the Russophone milieu – pragmatic, popularly geopolitical and counter-normative - are singled out and discussed.
Keywords: Russia's war in Ukraine; Estonia; Russophone diaspora